UJI PENGGUNAAN FORMULASI TRICHOKOMPOS TKKS DENGAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.)UMUR 8 – 12 BULAN ASAL KECAMBAH KEMBAR - Siahaan, Joel Fernando; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to know giving influence of formulations trichokompos TKKS with NPK fertilizerand get the best treatment of formulation for the growth of oil palm seeds (Elaeis guineensis Jacq.)which derived of multy embrio. This  research has  been  conducted  in  the Agriculture  Experimental  Station  Faculty  of  Agriculture,  University  of  Riau, District of Tampan, the research was  carried out for 4 months starting in April 2015  to  the  month  of Agustus 2015. This research arranged experimentaly using Completely Randomized Design (CRD)arranged in non-factorial, which consist of 5 treatment and 3 restating, so that entirely 15 attempt units. Every attempt unit consisted of 2 polybag crop and both as a sample, P0: Without fertilizer, P1:Trichokompos TKKS 10 ton/Ha (74,5 g/polybag) + NPK 2 tablet equel to 23,738 g/polybag. P2:Trichokompos TKKS ton/Ha (74,5 g/polybag) + NPK          4 tablet equel to 47,476 g/polybag. P3:Trichokompos TKKS ton/Ha (124,5 g/polybag) + NPK 2 tablet equel to 23,738 g/polybag. P4: Trichokompos TKKS ton/Ha (124,5 g/polybag) + NPK 2 tablet equel to 47,476 g/polybag. Analysis of variance result showing existence of reality difference, continued with tested to be continuation with deep experiment Duncans New Multiple Range Test (DNMRT)at level 5%. Based on research result which has been done indicates that giving various doses of formulations trichokompos TKKS with NPK fertilizer give an significantly effect on all parameters observed. From this research giving best influence at dose 124,5 g and 74,5 richokompos TKKS + 4 Tablet NPK on all parameter observed. The final results of observations to show that the average of high, number of leaves and cusps diameter on oil palm seeds origin multy embrio which aged 12 months has exceeded the growth standards issued by PPKS. So oil palm seeds of origin multy embrio worth for use as plant material.   Keywords:Oil palm, multy embrio, Trichokompos TKKS, NPK fertilizer.